Perlindungan Hukum Pemegang Hak Cipta Karya Digital Terhadap Praktik Pelanggaran Hak Cipta Digital - Ridhwan Listiyo Nugroho; Yudho Taruno Muryanto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to determine the form of protection of digital copyright holders against copyright infringement. This study is a normative legal study using primary and secondary legal materials. This study uses an approach in the form of a legislative approach and is analyzed using a syllogism with a deductive mindset. The results of this study indicate that copyright is an exclusive right of the creator that is obtained automatically after a creation is manifested in a tangible form without reducing restrictions in accordance with the provisions of laws and regulations. The use of technology makes it easy for people to search for and access the information they need. This technological advancement has also made copyright infringement through piracy increasingly rampant. One of the violations that occurs is piracy by re-uploading which occurs due to advances in technology and information. Copyright protection on various digital platforms is an obligation that must be considered by the public to protect digital works. Piracy often occurs on platforms that have features for sharing video content. The less good consequences that result are the practice of piracy by re-uploading.